ВИЗНАЧЕННЯ ОПТИМАЛЬНОЇ ГЕОМЕТРІЇ ОБМОТКИ ІНДУКТОРА, ЩО ПРИЗНАЧЕНИЙ ДЛЯ НАГРІВУ ВНУТРІШНІХ КІЛЕЦЬ БУКСОВИХ ПІДШИПНИКІВ КОЛІСНИХ ПАР ВАГОНІВ МЕТРОПОЛІТЕНУ - Жаркін, А.Ф.; Пазєєв, А.Г.; Бондар, О.І. (Інститут електродинаміки Національної академії наук України, 2024)
The process of high-frequency induction heating of the inner rings of bushing bearings before disassembly, which is carried out during the repair work of wheel pairs of subway cars, has been investigated. Physical modeling of the heating process was carried out at a frequency of 10 kHz and using an inductor with a three-row winding of 17 turns, the length of which was equal to the length of the ring. It is shown that when varying the heating time and the power transmitted to the part, it is not possible to ensure the selection of an acceptable heating mode for normal disassembly from the point of view of ensuring repeatability of results and preventing local overheating of the part. Calculations were carried out in the COMSOL environment on the finite element model of the process of heating the ring of a bushing bearing with a constant number of turns for different variants of the geometry of the inductor winding, that is, the number of winding rows, the number of turns in a row and their location relative to the inner rings of the bearings. It is shown that the geometric shape of the inductor winding has a significant effect on the distribution of specific heat emissions along the surface of the parts. The optimized geometry of the winding was determined, which ensures the necessary heating dynamics and the absence of local overheating zones of the bearing rings, which allows to reduce the proportion of rejected parts. Ref. 5, fig. 6, table.